Internalisation of external effects in European freight corridors - Anna Mellin; Åsa Wikberg; Inge Vierth; Rune Karlsson (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
External effects or externalities 'consist of the costs and benefits felt beyond or 'external to' those causing the effect' (Anderson, 2006). In the case of transportation, the negative externalities (costs) can take the form of air pollution, noise and accidents. Since external effects do not have a market price, external effects are a form of market failure. Wear and tear of the infrastructure is external to individual drivers and operators, and thus also included in the analysis...
Keywords: 330